Hematopoietic Stem Cell Niches and Signals Controlling Immune Cell Development and Maintenance of Immunological Memory - Miao, Runfeng; Lim, Vivian Y.; Kothapalli, Neeharika; Ma, Yifan; Fossati, Julia; Zehentmeier, Sandra; Sun, Ruifeng; Pereira, João P. (Frontiers in Immunology, 2020)
Studies over the last couple of decades have shown that hematopoietic stem cells (HSCs) are critically dependent on cytokines such as Stem Cell Factor and other signals provided by bone marrow niches comprising of mesenchymal stem and progenitor cells (MSPCs) and endothelial cells (ECs). Because of their critical roles in HSC maintenance the niches formed by MSPCs and ECs are commonly referred to as HSC niches. For the most part, the signals required for HSC maintenance act in a short-range manner, which imposes the necessity for directional and positional cues in order for HSCs to localize and be retained properly in stem cell niches. The chemokine CXCL12 and its Gi protein coupled receptor CXCR4, besides promoting HSC quiescence directly, also play instrumental roles in enabling HSCs to access bone marrow stem cell niches. Recent studies have revealed, however, that HSC niches also provide a constellation of hematopoietic cytokines that are critical for the production of most, if not all, blood cell types. Some hematopoietic cytokines, namely IL-7 and IL-15 produced by HSC niches, are not only required for lymphopoiesis but are also essential for memory T cell maintenance. Consequently, hematopoietic progenitors and differentiated immune cells, such as memory T cell subsets, also depend on the CXCL12/CXCR4 axis for migration into bone marrow and interactions with MSPCs and ECs. Similarly, subsets of antibody-secreting plasma cells also reside in close association with CXCL12-producing MSPCs in the bone marrow and require the CXCR4/CXCL12 axis for survival and long-term maintenance. Collectively, these studies demonstrate a broad range of key physiological roles, spanning blood cell production and maintenance of immunological memory, that are orchestrated by stem cell niches through a common and simple mechanism: CXCL12/CXCR4-mediated cell recruitment followed by receipt of a maintenance and/or instructive signal. A fundamental flaw of this type of cellular organization is revealed by myeloid and lymphoid leukemias, which target stem cell niches and induce profound transcriptomic changes that result in reduced hematopoietic activity and altered mesenchymal cell differentiation.